Individual and ensemble perception in naturalistic scenes: Effects of context and presentation time - Yanina E. Tena Garcia; Bianca R. Baltaretu; Katja Fiehler (PLoS ONE, 2026)
In many everyday tasks, we must identify both single objects, as well as object ensembles. Our understanding of the mechanisms behind individual and ensemble perception comes mainly from studies conducted under very simplistic conditions. Here, we aim to further this understanding by moving toward more naturalistic environments. We tested the influence of scene context and presentation time on individual and ensemble perception. Six kitchen objects were presented in two scene contexts, either a kitchen scene or in front of a texturized background for one of three presentation times (100, 800, or 3200 ms). After viewing the objects, participants were instructed to indicate via mouseclick the position of one of the six objects (Individual task) or their average, ensemble position (Ensemble task). We assessed task performance (mouseclicks and eye movements) separately for the two tasks. In the Individual task, objects were located with higher accuracy in the kitchen scene at the longer presentation times. The related eye movements, during initial scene viewing, showed more frequent and larger saccades in the kitchen scene, with no differences in peak velocity, and shorter fixations on individual objects. Increasing presentation time was associated with fewer, larger and slower saccades, as well as longer object fixations. In the Ensemble task, the ensemble position was located more accurately in the texturized background when it was shown briefly (100 ms). Eye movements in the naturalistic scene revealed more frequent, larger and slower saccades, and shorter fixations on the ensemble position. Moreover, increasing presentation time showed fewer, smaller, and slower saccades, with longer fixations on the ensemble region. Overall, we found that scene context and presentation time influence spatial localization and eye movement behavior in individual and ensemble perception, highlighting the need to consider such contextual factors in future work.